Revolution Detroit : Strategies for Urban Reinvention - Gallagher, John, 1949- (Book collections on Project MUSE., 2013)
After weathering decades of suburban sprawl, job loss, and lack of regional government, Detroit has become a symbol of post-industrial distress and also one of the most complex urban environments in the world. The author argues that Detroit's experience can offer valuable lessons to other cities that are, or will soon be, dealing with the same broken municipal model. -- Back cover.